Hubungan Dukungan Keluarga Terhadap Keikuitsertaan Wanita Usia Subur pada Program KB di UPTD Puskesmas Kuta Baharu Kota Baharu Kabupaten Aceh Singkil Provinsi Aceh Tahun 2024 - Supri Supri; Dewi Sartika Hutabarat; Edi Subroto; Astaria Br.Ginting; Henni Sihombing; Else Situmorang (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The population explosion resulted in a rapid rate of population growth which was caused by a lack of knowledge and patterns in the local community. Important aspects of population are: population size, population growth, population births, and population movements. This study aims to analyze the relationship between family support and the participation of women of childbearing age in the Family Planning (KB) program at the UPTD Puskesmas Kuta Baharu, Kota Baharu, Regency. This research used a quantitative method with a survey approach, involving 100 female respondents of childbearing age who were randomly selected. Data was collected through a questionnaire that measured the level of family support and participation in family planning programs. Data analysis was carried out using Pearson correlation statistical techniques to identify the relationship between family support and participation in family planning programs. The research results show that there is a significant relationship between family support and the participation of women of childbearing age in family planning programs, with a p value <0.05. These findings indicate that family support plays an important role in increasing women's participation in family planning programs. This research suggests that family planning programs should involve family members more in socialization and education to increase participation levels.